Main stages of tourism development - Elyubaev R. B., Shaykhygaliev E. A. (Interactive science, 2016)
this article considers the main stages of tourism development and formation, starting from the ancient era till the first tourist company was found, Moreover, the article determines major causing factors of tourism development.
Keywords: история; туризм; путешествие; античность; транспортные средства; Tourism; history; trips; ancientness; transport services